Improving geometry transformation thinking skills using student activity sheets based on discovery-contextual learning based on Van Hiele's theory - Nofyta Arlianti; Kamid Kamid; Jefri Marzal; Muhammad Haris Effendi Hasibuan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Geometry thinking ability is the ability of students in terms of observing objects, building definitions based on the characteristics inherent in the object, recognizing the relationship between one object with other objects, and applying it in solving geometry problems. However, the ability to think geometry students are still low. This is because students are still dependent on lecturers in receiving information and learning that occurs in the classroom has not facilitated the ability to think geometry, especially geometry transformation. For this reason, a student activity sheet based on Discovery- Contextual Learning based on van hiele theory was developed which is effective in improving the geometry thinking ability of mathematics education students of STKIP Muhammadiyah Sungai Penuh. The subjects of this study were 5th semester students of mathematics education. The development model used is adapted from the Plomp model. There are three stages in this model, namely preliminary research, prototype phase, and assessment. This study focused on seeing the effectiveness of the product at the assessment stage. The assessment phase was carried out on a field test consisting of 13 students for 9 meetings. The syntax of this learning model includes: 1) Stimulation, 2) Constructivism, 3) Problem Statement, 4) Data Collection, 5) Learning Community, 6) Modeling, 7) Data Processing, 8) Verification, 9) Reflection, and 10) Authentic Assessment.